Managing Africa’s Natural Resource Endowments: New Dispensations And Good-Fit Approaches - Hanson, Kobena T. (Journal of Sustainable Development Law and Policy, 2025)
Managing a nation’s extractive natural resource endowments can advance national development if done meaningfully. Unfortunately, across Africa, the apparent mismanagement of such resources, poor growth rates, social tensions, and civil strife in resource-rich countries have thrown up a great deal of literature on what is now known as resource curse.It has also ignited calls for enhanced governance and improved capacities for the myriad of actors engaged in natural resource extraction. This article draws on the extant literature to interrogate the complex entanglements of issues involved in the natural resource value chain in Africa. It argues that in spite of the general ills, economic challenges, and socio-political pains that resource-rich African nations face in exploiting and managing their natural resources, the extractive industry in Africa is evolving positively, and that the situation of resource-rich African states is not immutable. Available evidence suggests that Africa is emerging a new, more complex, participatory, and coordinated vision of NRM; a development that offers opportunities and possibilities for Africa to engage emerging actors especially in the global South. The article concludes that what Africa needs is an approach with a good fit to local realities, and an enhancement of individual and institutional capacities.